Intellectual Property as An Object of Banking Credit Collateral in The Digital Era - Nanda Dwi Riskia; Hardi Fardiansyah (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
Banks must adhere to the fiduciary and prudential principles in their management as a financial institution whose operational activities are channelling and storing funds to and from the public. Every banking institution operating in Indonesia must go hand in hand with implementing the national development program. This statement is also in line with the objectives of the bank that must be achieved, one of which is to support the implementation of national development as outlined in Article 4 of the Banking Law. Because of this, the function and purpose of banking institutions is to manage public funds and expedite the implementation of national economic development. Research Methods uses normative juridical research methods, a process to find legal rules, principles and doctrines to answer the legal issues at hand. The results of research on HKI credit as an object of bank credit guarantees and revisions regarding Bank Indonesia Regulation (PBI) No. 9/6/PBI/2007 concerning Asset Quality Rating for Commercial Banks related to credit collateral is one of the main factors why the bank has not been able to accept IPR as the object of bank credit guarantees. To realize this renewal concept, strict and detailed juridical support regarding IPR assets as objects of bank credit guarantees, comprehensive outreach, and an IPR appraisal institution in Indonesia are needed.